Division Of Inheritance Law and Employment Law - Fatihan Haykal (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The problem raised in this research is the distribution of inheritance law in Indonesia in relation to the diversity of applicable legal systems, as well as the implementation of labor law in protecting workers' rights. In terms of inheritance law, there are differences between customary inheritance law, Islamic inheritance law and civil inheritance law which sometimes give rise to disputes related to the distribution of inherited assets. Meanwhile, in the field of labor law, although regulations have regulated the protection of workers' rights, implementation challenges related to industrial disputes and protection of informal workers are still issues that have not been fully resolved. The aim of this research is to analyze the legal distribution of heirs in Indonesia as well as the application of labor law which can better protect workers' rights. This research is normative juridical research that uses a statutory approach and qualitative descriptive analysis. The results of the research conclude that the legal system for heirs in Indonesia needs harmonization between customary law, Islamic law and civil law in order to resolve inheritance disputes more effectively. Meanwhile, in labor law, although there have been efforts to protect workers' rights through regulations such as the Job Creation Law, there is still an imbalance in its application to informal and outsourced workers who are at risk of losing the protection of their rights